PENGARUH BRAND IMAGE DAN BRAND TRUST TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PRODUK SMARTPHONE INFINIX DI SUZUYA TANJUNG MORAWA - Tampubolon, Rhoni Ilham (Juripol (Jurnal Institusi Politeknik Ganesha Medan), 2024)
This study aims to find out "The Effect of Brand Image and Brand Trust on Smartphone INFINIX Suzuya Tanjung Morawa Product Consumer Purchase Decisions". This type of research is associative. The population in this study were all consumers of Smartphone INFINIX Suzuya Tanjung Morawa Products as many as 180 customers using Slovin formula techniques, then the number of samples in this study were 124 respondents taken from a portion of the population. Based on the results of the t test it can be seen that the tcount on the variable Brand Image and Brand Trust is 3,620 and 5,273> t table is 1,657 with probability t that is sig <0,05 towards the variable loyalty. Based on the results of the F test, the calculated F value is 28.383> 3.07 with sig 0,000 <a0.05, indicating that the Brand Image and Brand Trust simultaneously have a positive and significant effect on the Purchase Decision variable. The Adjusted R Square value obtained is 0.308 or 30.8%. loyalty can be explained by Brand Image and Brand Trust, the remaining 59.8% is influenced by other factors not explained in this study.